COMMUNITY PARTICIPATION ON WASTE BANK TO FACILITATE SUSTAINABLE SOLID WASTE MANAGEMENT IN A VILLAGE - Rachman, Indriyani; Komalasari, Nia; Hutagalung, Ira Rumiris (UI Scholars Hub, 2021)
Community participation is required for managing solid waste. In Indonesia, community acceptance and participation in solid waste management are assessed by the presence of a waste bank at the village or neighborhood level. This study aimed to find out the source, economic potency, and handling system of solid waste in a village setting. This study took place at Ketapang Village, Mauk Sub District, Tangerang Regency, Indonesia. This study evaluated the community participation in the waste bank in Ketapang Village, which is called, Sakumis Bersalaman Waste Bank, and its potential to manage solid waste and generate some profits for the community. Some steps were performed to obtain the answer to the research question. A desk review was conducted to analyze the current waste management practice. Solid waste generation data was taken from an 8-days survey of the collected waste managed by the waste bank. In-depth interviews with 96 households were conducted to find out the potential of future waste bank development. It was found that from 1,988 households in Ketapang Village only 448 households participated in Sakumis Bersalaman Waste Bank. Based on the results of the analysis on the questionnaire which was distributed randomly to 182 households which are communities around the waste bank, it was found that 51.4% of respondents were not yet members of the waste bank. From this percentage, 94.4% of them declared that they want to be waste bank members. It is suggested to Shakumis Bersalaman Waste Bank to add members so that more waste will be recycled. In this way, the community will receive more benefits. From the results, we concluded that community participation through a waste bank, especially a better waste management system, is the potential way to increase the economic level of the village. Moreover, a waste bank could facilitate better solid waste management and produce a sustainable circular economy at the village level.